The Impact of Information Management Systems on Supervision and Control of Construction Projects - Hafnidar A. Rani; Jurisman Amin; Luthfi Aldiansyah Irawan; Muhammad Shafly Aqsha (LPPM Institut Teknologi Adhi Tama Surabaya (ITATS), 2025)
Construction projects frequently encounter supervision and control challenges, leading to delays and cost overruns, primarily due to inadequate information management. This study examines the impact of Information Management Systems (IMS) adoption on project supervision and control in Banda Aceh, with a focus on information quality, technological readiness, and user competency. Using a quantitative survey of 95 construction professionals and multiple linear regression analysis, the findings reveal that IMS enhances real-time data accessibility, transparency, and process integration. However, its effectiveness depends on technological infrastructure, user training, and management support. These insights offer strategic recommendations for optimizing IMS adoption to improve project performance.